A classification of the aquatic Podostemaceae subfamily Tristichoideae, with a new genus based on ITS and matK phylogeny and morphological characters. Issue 2 (17th January 2022) - Koi, Satoshi; Uniyal, Prem Lal; Kato, Masahiro
Abstract: The submerged lithophilous Podostemaceae show remarkable variation in phenotypic characters. Taxonomic estimation of the characters alone may not have produced a natural classification of subfamily Tristichoideae. Among the genera, Cussetia and Indotristicha have not been examined by detailed morphological observations and molecular analyses. The present ITS and/or matK phylogenies indicated that Cussetia carinata is close to Terniopsis with high support, and Indotristicha tirunelveliana and Dalzellia form a clade with robust support, while the congeneric I. ramosissima was separated from the clade. Cussetia differs from Terniopsis by having many, alternately 3‐whorled, carinate bracts and heteromorphic shoots, whereas they share the capped root and 3‐stichous leaves. The habitat of C. carinata is the deepest under water in the family. Indotristicha tirunelveliana differs from Dalzellia in the holdfasts, shoots, ramuli, phyllotaxis and cupules. Based on the consistent phylogeny and morphological variation, the genus Cussetia is accepted and a new genus for I. tirunelveliana is proposed. The emended seven genera were characterized primarily by vegetative characters. Tabulated diagnostic characters, a synopsis and a key to genera is presented.